Web-Based SME Online Marketing System (E-Commerce) - M Syafrizal (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2021)
The objectives of this research are; 1) To find out the Web-based SME Online Marketing System (E-Commerce), and 2) To design a web-based SME Online Marketing System (E-Commerce). Data Flow Diagram (DFD) is used to design the application, while the application design stage uses the Rapid Application Development (RAD) method. Based on the results of the research the author can draw a conclusion which includes the following; 1) The use of an online marketing system for SMEs (e-Commerce) based on the Web is expected to help create accurate and effective Sales Information data, 2) The information system provides convenience for SMEs because it speeds up information in general and reduces errors, 3) System Sales Information on SMEs which the author designed uses various web-based programming languages ​​consisting of; HTML, CSS, Jquery, JavaScript, JSON PHP, and for database processing the Structure Query Language (SQLi) is used. The supporting software used is XAMPP version 5.6 (Support MySQLi), NotePad ++, and Google Chrome Browser, and 4) Sales Information System for SMEs which the author designed also uses several APIs such as; WhatsApp Auto-Order link, GMAIL SMTP, Raja Ongkir Courier API which is a third party as a supporter of this sales application.